2023
DOI: 10.1021/acsenergylett.3c01722
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Lewis-Acid-Strength Cation Cs+-Doped Double Perovskite for Fast and Durable Oxygen Reduction/Evolutions on Protonic Ceramic Cells

Yangsen Xu,
Kang Xu,
Feng Zhu
et al.

Abstract: Improving the reaction kinetics and durability of air electrodes on protonic ceramic cells is effective for their commercialization but challenging. Here, we report our electrode design via a low-Lewis-acid-strength cation (Cs+) doping strategy on a double perovskite oxide with a detailed formula of PrBa0.9Cs0.1Co2O5+δ (PBCsC). At 600 °C, the PBCsC electrode demonstrates a low area-specific resistance (ASR) value of 0.3 Ω cm2 within 100 h without significant degradation due likely to the electron pair shift by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 68 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…2d, the O 1s spectrum likely exhibits four peaks at binding energies of 529, 530, 532, and 534 eV, respectively, corresponding to lattice oxygen (O lat ), high oxidation oxygen (O ho ), adsorbed oxygen (O ads ), and adsorbed water (H 2 O ads ). 46 It has been reported that the ratio of adsorbed oxygen to lattice oxygen can be used to assess the oxygen reaction activity of an electrode material. 47 A higher O ads /O lat ratio may indicate a higher ORR activity accordingly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2d, the O 1s spectrum likely exhibits four peaks at binding energies of 529, 530, 532, and 534 eV, respectively, corresponding to lattice oxygen (O lat ), high oxidation oxygen (O ho ), adsorbed oxygen (O ads ), and adsorbed water (H 2 O ads ). 46 It has been reported that the ratio of adsorbed oxygen to lattice oxygen can be used to assess the oxygen reaction activity of an electrode material. 47 A higher O ads /O lat ratio may indicate a higher ORR activity accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…For example, at 800 °C SCN–PSCN shows and values of 1.22 × 10 −3 cm s −1 and 3.73 × 10 −4 cm 2 s −1 , respectively; these values are analogous to recently reported high-performance air electrodes. 13,46 To investigate more details of oxygen reaction kinetics on the SCN–PSCN electrode, we collected EIS of the SCN–PSCN air electrode with different oxygen partial pressures ( p O 2 ) at 700 °C. The EIS measured at different partial pressures of oxygen (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to its higher mixed ionic-electronic conductivity and oxygen surface exchange coefficient, cobaltite-based perovskite/double perovskite air electrodes such as La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3−δ (LSCF) , and LnBaCo 2 O 5+δ (LnBC, Ln = rare earth metals) have been extensively researched for use in IT-SOCs. Compared with the state-of-the-art LSCF air electrode, LnBC offers faster oxygen surface exchange and bulk diffusion kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the economic competitiveness of SOFCs technology, a general strategy is to reduce the operating temperatures to an intermediate temperature range (600–800 °C). , However, as the operating temperature is reduced, the polarization resistance of electrodes, especially cathodes, is greatly increased, resulting in an insufficient power output of SOFCs at intermediate temperatures. To date, continuous innovative design strategies of perovskite-type cathodes have been applied to develop a series of mixed ionic–electronic conductors (MIECs) with high electrocatalytic activity for the oxygen reduction reaction (ORR), such as La x Sr 1– x Co y Fe 1– y O 3−δ (LSCF), Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ (BSCF), and LnBaCo 2 O 5+δ (Ln = lanthanide elements). , It is generally accepted that typical alkaline-earth metal ions (e.g., Ba 2+ , Sr 2+ , and Ca 2+ ) with larger ionic size and lower oxidation state are often doped into the A-site of perovskite-type oxides to introduce more oxygen vacancies, thus accelerating the ORR kinetics . However, detrimental effects of enrichment or segregation of these alkaline-earth metal elements (driven by the electrostatic interactions and elastic energy minimization) on the cathode surface or the cathode–electrolyte interface under realistic operating conditions have been widely observed and reported .…”
mentioning
confidence: 99%